2001
DOI: 10.2166/wst.2001.0158
|View full text |Cite
|
Sign up to set email alerts
|

Biological nutrient removal in a full-scale SBR treating piggery wastewater: results and modelling

Abstract: Research activities carried out at ENEA during the last few years allowed development of a Sequencing Batch Reactor (SBR) that is able to remove biologically organic waste, nitrogen and phosphorus and that showed to be particularly suited to obtain low effluent nutrient concentrations even starting from concentrated wastes. This plant, in more than one year of operation, is quite steadily obtaining more than 98% removal of nitrogen, phosphorus and COD. On the basis of the experimental results, a simulation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Oles and Wilderer [15] modified the deamination rate parameter of dissolved organic nitrogen under aerobic and anoxic condition, the modified model can predicted the variation of COD, ammonia, nitrate in the operation process of the SBR process. Based on the unsuitable assumption of one step process of nitrification and denitrification, some study split the nitrification and denitrification into two-step reaction [16,17]. At the same time, Brenner [18] modified ASM2 model to establish the nitrogen and phosphorus transform model by changing facultative coefficient in order to control the initial states of nitrification and denitrification.…”
Section: Research Progress Of Asm Modelmentioning
confidence: 99%
“…Oles and Wilderer [15] modified the deamination rate parameter of dissolved organic nitrogen under aerobic and anoxic condition, the modified model can predicted the variation of COD, ammonia, nitrate in the operation process of the SBR process. Based on the unsuitable assumption of one step process of nitrification and denitrification, some study split the nitrification and denitrification into two-step reaction [16,17]. At the same time, Brenner [18] modified ASM2 model to establish the nitrogen and phosphorus transform model by changing facultative coefficient in order to control the initial states of nitrification and denitrification.…”
Section: Research Progress Of Asm Modelmentioning
confidence: 99%
“…They ranged from 15% to 95%. The literature on total COD removal efficiencies using sequencing batch reactors for piggery wastewater treatment also reports very variable results, ranging from 64% (Obaja et al 2003) to 98% (Tilche et al 2001). However, the effluent COD was still quite high for both total and soluble COD (average COD effluent concentrations were ca.…”
Section: Biological Analysesmentioning
confidence: 99%
“…The composition of piggery wastewater shows a great variation according to the farm of origin (Boursier et al 2005). Specifically, the concentration of ammonia nitrogen and total chemical oxygen demand (COD) in physically pre-treated piggery wastewater ranges from 250 to 1,650 mg L −1 and from 4,000 to 6,000 mg L −1 , respectively (Tilche et al 2001;Obaja et al 2003;Ra et al 2000). However, one of the most frequently used of all the technologies available for biologically removing nutrients and organic matter from piggery wastewater is sequencing batch reactor (SBR) (Obaja et al 2003;Ra et al 2000;Tilche et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Andreottola et al [4] reported the results of system optimization through on line monitoring and control of pH, ORP and DO for an SBR operated with triple anoxic filling phases of equal duration. Tilche et al [5] tested an SBR with five subcycles, each with 2 h anoxic and 2 h aerobic periods for the treatment of piggery wastewater with a very high nitrogen content. Puig et al [6] also described a successful implementation in the SBRs using 4-6 filling events with a sequence of anoxic-aerobic phases treating synthetic and urban wastewater.…”
Section: Introductionmentioning
confidence: 99%